2021
DOI: 10.3390/ijms22168783
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer and Electrochemical Properties of Thiogenistein—New Biologically Active Compound

Abstract: Pharmacological and nutraceutical effects of isoflavones, which include genistein (GE), are attributed to their antioxidant activity protecting cells against carcinogenesis. The knowledge of the oxidation mechanisms of an active substance is crucial to determine its pharmacological properties. The aim of the present work was to explain complex oxidation processes that have been simulated during voltammetric experiments for our new thiolated genistein analog (TGE) that formed the self-assembled monolayer (SAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Additionally, it was confirmed that the potency of the antitumor activity of genistein and its derivatives varies in different tumor types, depending on their selectivity for the target molecules. Our previous studies have shown that the substitution of the -OH group at position seven of the A ring by an ethyl linker and a thioglycolic acid residue allows us to obtain a derivative showing a higher cytotoxic activity against human prostate cancer DU145 cells, but also a lower toxicity against normal prostate epithelial cells (PNT2) compared to its precursor–genistein [ 20 ]. Based on previous promising results, our research has been extended to include two breast cancer lines: the estrogen-positive MCF-7 and the estrogen-negative MDA-MB-231.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, it was confirmed that the potency of the antitumor activity of genistein and its derivatives varies in different tumor types, depending on their selectivity for the target molecules. Our previous studies have shown that the substitution of the -OH group at position seven of the A ring by an ethyl linker and a thioglycolic acid residue allows us to obtain a derivative showing a higher cytotoxic activity against human prostate cancer DU145 cells, but also a lower toxicity against normal prostate epithelial cells (PNT2) compared to its precursor–genistein [ 20 ]. Based on previous promising results, our research has been extended to include two breast cancer lines: the estrogen-positive MCF-7 and the estrogen-negative MDA-MB-231.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies would suggest that changing the hydroxyl for an ether containing an –SH group on the C7 carbon in the A ring may increase the cytotoxic properties of TGE. This effect can be attributed to the presence of a highly reactive -SH group [ 20 , 28 ]. Marik and coworkers also proved that the substitution of the -OH group at position seven of the A ring by aliphatic chains and heterocyclic 1,2,3-triazole moieties enhances the cytotoxic properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacological actions of isoflavones of natural origin, such as genistein (GE), relate to their antioxidant activity, and they protect cells from carcinogenesis. Using a self-assembled monolayer on the gold electrode in simulated voltammetry, Stolarczyk et al [ 3 ] have revealed that a new thiolated genistein analog (TGE) has antioxidant activity. The electroactive centers of TGE and its oxidation mechanism have been elucidated using infrared spectrometry supported by quantum chemical and molecular mechanics calculations.…”
mentioning
confidence: 99%